Polymer-MXene-polymer heterostructure nanosheet and preparation method thereof

By performing polymerization and calcining treatment on two-dimensional MXene nanosheets, polymer-MXene-polymer heterostructure nanosheets with mesoporous structures were constructed, solving the problem of two-dimensional porous heterostructure integration and achieving efficient preparation of absorbing materials.

CN119503771APending Publication Date: 2025-02-25XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411647039.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to integrate two-dimensional structures and single-layer porous structures into a hybrid material, resulting in the construction of two-dimensional porous heterostructures having great challenges.

Method used

By mixing the template agent and the reaction solvent, adding two-dimensional MXene nanosheets and resin in sequence for polymerization, followed by calcination treatment, and using the self-assembly and hydrogen bonding of the resin and the template agent, a polymer-MXene-polymer heterostructure nanosheet with a mesoporous structure was constructed.

Benefits of technology

The two-dimensional structure and single-layer porous structure are integrated into a hybrid material, which improves the specific surface area and wave absorption capacity of the material. This method is simple and easy to perform, has high yields, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503771A_ABST
    Figure CN119503771A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer-MXene-polymer heterostructure nanosheet and a preparation method thereof, and belongs to the technical field of two-dimensional metal materials. According to the method disclosed by the invention, after the template agent and the reaction solvent are mixed, the two-dimensional MXene nanosheet and the resin are sequentially added for a polymerization reaction, then calcination treatment is carried out, in the preparation process, the resin is converted into carbon, the carbonization degree can be controllably adjusted through the reaction temperature, and the preparation process is simple. According to the method, a two-dimensional structure and a single-layer porous structure can be integrated into one hybrid material, and the method is simple and easy to implement, high in yield and high in yield and can realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of two-dimensional metal materials, and specifically relates to a polymer-MXene-polymer heterostructure nanosheet and a preparation method thereof. Background Art

[0002] With the rapid development of electronic information technology, various electronic communication devices have brought great convenience to people, but also caused harm to people's living environment and health. Microwave absorbing materials are not only used in military stealth, confrontation and anti-confrontation, but also in human safety protection, electromagnetic interference of communication and navigation systems, elimination of microwave darkrooms, confidentiality of security information and many other aspects. Therefore, the development of high-performance microwave absorbing materials has become one of the main research directions. The most widely studied microwave absorbing materials are carbon materials, because they have both dielectric loss capacity and resistive loss capacity, and are light in weight, adjustable dielectric properties, good conductivity, high temperature resistance and good chemical stability. Among these carbon-based materials, porous carbon-based materials are considered to be a practical and effective electromagnetic wave absorbing material. On the one hand, the porous structure can reduce the density of the material and increase the specific surface area, thereby realizing the lightweight of the absorbing material. On the other hand, the porous structure can provide a semi-closed environment, which is conducive to multiple reflections and scattering of electromagnetic waves, and prolongs the dissipation path of electromagnetic waves. However, the electromagnetic parameters of the porous structure are still unbalanced due to the impedance matching with the free space, and it is difficult to adjust accurately. Therefore, it is very necessary to develop a new porous carbon absorbing material with a suitable pore structure and low size.

[0003] In recent years, great efforts have been devoted to the development of novel two-dimensional (2D) materials due to their attractive physicochemical properties and broad application prospects, such as in energy storage and conversion. Two-dimensional metal carbides and nitrides, known as MXenes, have excellent electrical conductivity, good hydrophilicity, tunable surface functional groups, and unique layered structures. However, due to the van der Waals force, 2D MXene nanosheets are easily stacked, resulting in limited accessibility within them, which in turn restricts their usability as active materials. Therefore, it is an attractive goal to construct 2D porous heterostructures by creating mesopores in 2D nanosheet materials, which endows 2D nanosheets with rich and interconnected pore networks, increasing the specific surface area and thus enhancing the absorption capacity. In addition, based on the synergistic effect between MXene and porous carbon, 2D heterostructures can also show extraordinary performance. However, due to methodological limitations, the synthesis of 2D porous MXene heterostructures with comprehensive functionality and porosity is very scarce, and the synthesis of 2D heterostructures composed entirely of porous monolayers is even more challenging. The construction of 2D porous heterostructures relies on a coated porous layer with a well-matched interface, which requires a proper affiliation with micelles to achieve heterogeneous growth while precisely controlling the assembly of micelles. Therefore, it remains a great challenge to design and fabricate a 2D porous heterostructure that cleverly integrates 2D structures and monolayer porous structures into one hybrid material. Summary of the invention

[0004] The purpose of the present invention is to provide a polymer-MXene-polymer heterostructure nanosheet and a preparation method thereof, so as to solve the technical problem that the existing method is difficult to achieve a two-dimensional porous heterostructure integrating a two-dimensional structure and a single-layer porous structure into a hybrid material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a polymer-MXene-polymer heterostructure nanosheet, comprising the following steps: After the template and the reaction solvent are mixed, two-dimensional MXene nanosheets and resin are added in sequence to obtain a reaction solution, and the reaction solution is subjected to a polymerization reaction; after the reaction is completed, the obtained reaction product is subjected to post-treatment and calcination treatment in sequence to obtain polymer-MXene-polymer heterostructure nanosheets.

[0006] Further, the template agent is a surfactant; The surfactant is one of hexadecylaminomethane, sodium α-olefin sulfonate, sodium linear alkylbenzene sulfonate, sodium α-sulfonated fatty acid methyl ester (mono) sodium salt, fatty acid polyoxyethylene ester, Pluronic P-123 and Pluronic F-127; The resin is one or more of polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, dopamine and phenolic resin.

[0007] Furthermore, the reaction solvent is water.

[0008] Furthermore, the mass concentration of the resin in the reaction solution is 0.5-10 g / L.

[0009] Furthermore, the mass concentration of the template in the reaction solution is 1-10 g / L.

[0010] Furthermore, during the polymerization reaction, the mass concentration ratio of the resin to the template is 0.1-100.

[0011] Furthermore, the polymerization reaction temperature is 25-80°C and the time is 2-72 h.

[0012] Furthermore, the calcination treatment is carried out in an inert atmosphere; the temperature of the calcination treatment is 300-1800° C., and the time is 1-24 h; the inert atmosphere is nitrogen or argon.

[0013] Furthermore, the post-processing includes centrifugation and drying processes performed sequentially.

[0014] The present invention also discloses a polymer-MXene-polymer heterostructure nanosheet prepared by the above preparation method.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a polymer-MXene-polymer heterostructure nanosheet. After a template agent and a reaction solvent are mixed, two-dimensional MXene nanosheets and resin are added in sequence to carry out polymerization reaction, followed by calcination treatment. During the preparation process, the resin and the template agent are self-assembled into cylindrical micelle bundles as building units with the help of hydrogen bonds. Secondly, the single-layer single micelles are orderly adhered and assembled on both sides of a substrate through a close stacking arrangement process to achieve a state of minimum energy. Since there are a large number of oxygen-rich and nitrogen-rich groups in the substrate and the micelles, non-covalent interactions, especially hydrogen bonds, promote this process. In addition, along with the condensation process of the resin, a resin micelle polymer is formed in the gap between the MXene and the micelles to form a two-dimensional mesoporous composite nanosheet. Finally, by calcination, a two-dimensional mesoporous carbon composite nanosheet is obtained, wherein the resin is converted into carbon, and the degree of carbonization can be controllably adjusted by the reaction temperature. The method can integrate the two-dimensional structure and the single-layer porous structure into a hybrid material. The method is simple and easy to operate, has high yield and high output, and can realize large-scale production.

[0016] The present invention also discloses a polymer-MXene-polymer heterostructure nanosheet prepared by the above-mentioned preparation method. According to relevant experimental results, it can be proved that the prepared polymer-MXene-polymer heterostructure nanosheet has the characteristics of a two-dimensional switch-like structure, ordered mesopores parallel to the surface, a large surface area and easy surface modification, and has potential applications in the fields of biopharmaceuticals, separation and purification, analysis and monitoring, and flat panel displays. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 TEM image (10 μm) of the two-dimensional mesoporous composite nanosheet prepared in Example 1 of the present invention; Figure 2 TEM image (100 μm) of the two-dimensional mesoporous composite nanosheet prepared in Example 1 of the present invention; Figure 3 TEM image (500 μm) of the two-dimensional mesoporous carbon composite nanosheet prepared in Example 1 of the present invention; Figure 4 is a TEM image (100 μm) of the two-dimensional mesoporous carbon composite nanosheet prepared in Example 1 of the present invention; Figure 5 TEM image of the two-dimensional mesoporous composite nanosheet prepared in Example 2 of the present invention; Figure 6 TEM of the two-dimensional mesoporous carbon composite nanosheet prepared in Example 2 of the present invention; Figure 7 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Example 3 of the present invention; Figure 8 This is the TEM of the two-dimensional mesoporous carbon composite nanosheet prepared in Example 3 of the present invention; Fig. 9 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Example 4 of the present invention; Fig.10 This is the TEM of the two-dimensional mesoporous carbon composite nanosheet prepared in Example 4 of the present invention; Fig.11 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Comparative Example 1 of the present invention; Fig.12 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Comparative Example 2 of the present invention; Fig.13 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Comparative Example 3 of the present invention; Fig.14 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Comparative Example 4 of the present invention; Fig.15This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Comparative Example 5 of the present invention; Fig.16 This is the TEM of the two-dimensional mesoporous composite nanosheet prepared in Comparative Example 6 of the present invention; Fig.17 Reflection loss diagram of the two-dimensional mesoporous composite nanosheet obtained in Example 1 as an absorbing material; Among them: a-3D schematic diagram of reflection loss; b-2D schematic diagram of reflection loss. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0023] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0024] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0025] Example 1 A method for preparing a polymer-MXene-polymer heterostructure nanosheet comprises the following steps: Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water. Stir at 40 °C for 2 h, then add 120 mg of two-dimensional MXene nanosheet powder. After stirring at 40 °C for 1 h, add 100 mg of polyvinyl alcohol and continue stirring for 1 h. Adjust the pH value of the solution to 8.5 to initiate the polymerization reaction. Stir for 8 h to obtain a reaction product. Centrifuge and dry the reaction product to obtain a two-dimensional mesoporous composite nanosheet. Place 1 g of the two-dimensional mesoporous composite nanosheet in a crucible, put it in a tubular furnace filled with nitrogen, and carbonize (calcine) at 800 °C for 4 h. After cooling to room temperature, polymer-MXene-polymer heterostructure nanosheets (two-dimensional mesoporous carbon nanosheets) are obtained.

[0026] The transmission electron microscopy (TEM) image of the two-dimensional mesoporous composite nanosheet prepared in this example is as follows: Figure 1 and Figure 2 As shown by Figure 1 and Figure 2 It can be seen that the prepared material has good dispersion and uniformity, and has a mesoporous structure with a mesopore diameter of about 7 nanometers. The prepared polymer-MXene-polymer heterostructure nanosheets have the characteristics of two-dimensional switch-like structure, ordered mesopores parallel to the surface, large surface area and easy surface modification.

[0027] The two-dimensional mesoporous composite nanosheets prepared in this example are calcined at high temperature in a nitrogen atmosphere to obtain two-dimensional mesoporous carbon composite nanosheets. The TEM image is as follows Figure 3 and Figure 4 As shown, it indicates that the carbon material obtained after high-temperature calcination maintains the original structure, uniformity and dispersibility, and the mesopore size is slightly reduced.

[0028] Example 2 Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water, stir at 40 °C for 2 h, then add 120 mg of MXene powder, stir at 40 °C for 1 h, add 100 mg of polyvinyl chloride, and continue stirring for 1 h; adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h; after centrifugation and drying, two-dimensional mesoporous composite nanosheets are obtained; place 1 g of two-dimensional mesoporous composite nanosheets in a crucible, put it into a tubular furnace with nitrogen, and carbonize (calcinate) at 800 °C for 4 h, and wait for cooling to room temperature to obtain polymer-MXene-polymer heterostructure nanosheets (two-dimensional mesoporous carbon nanosheets).

[0029] The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this example are as follows: Figure 5 As shown, it can be seen that the prepared material has good dispersibility and uniformity, and has a mesoporous structure with a mesopore diameter of about 7 nanometers.

[0030] The two-dimensional mesoporous composite nanosheets prepared in this example are calcined at high temperature in a nitrogen atmosphere to obtain two-dimensional mesoporous carbon composite nanosheets. The TEM image is as follows Figure 6 , indicating that the carbon material obtained after high-temperature calcination maintained its original structure, uniformity and dispersibility, and the mesopore size was slightly reduced.

[0031] Example 3 Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water, stir at 40 °C for 2 h, then add 120 mg of MXene powder, stir at 40 °C for 1 h, add 100 mg of polyvinylidene chloride, and continue stirring for 1 h; adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h. After centrifugation and drying, a two-dimensional mesoporous composite nanosheet is obtained; 1 g of the two-dimensional mesoporous composite nanosheet is placed in a crucible, placed in a tubular furnace with nitrogen, and carbonized (calcined) at 800 °C for 4 h, and wait for cooling to room temperature to obtain a polymer-MXene-polymer heterostructure nanosheet (two-dimensional mesoporous carbon nanosheet).

[0032] The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this example are as follows: Figure 7 As shown, it can be seen that the prepared material has good dispersion and uniformity, has a mesoporous structure, and the mesopore diameter is increased to 10 nanometers. The two-dimensional mesoporous composite nanosheet prepared in this embodiment is calcined at high temperature in a nitrogen atmosphere to obtain a two-dimensional mesoporous carbon composite nanosheet. The TEM image is as follows Figure 8 As shown, it indicates that the carbon material obtained after high-temperature calcination maintains the original structure, uniformity and dispersibility, and the mesopore size is slightly reduced.

[0033] Example 4 Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water, stir at 40 °C for 2 h, then add 120 mg of MXene powder, stir at 40 °C for 1 h, add 100 mg of phenolic resin, and continue stirring for 1 h; adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h; after centrifugation and drying, two-dimensional mesoporous composite nanosheets are obtained; place 1 g of two-dimensional mesoporous composite nanosheets in a crucible, put it into a tubular furnace with nitrogen, and carbonize (calcinate) at 800 °C for 4 h, and wait for cooling to room temperature to obtain polymer-MXene-polymer heterostructure nanosheets (two-dimensional mesoporous carbon nanosheets).

[0034] The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this example are as follows: Fig. 9 As shown, it can be seen that the prepared material has good dispersion and uniformity, and has a mesoporous structure with a mesopore diameter of about 12 nanometers. The two-dimensional mesoporous composite nanosheet prepared in this embodiment is calcined at high temperature in a nitrogen atmosphere to obtain a two-dimensional mesoporous carbon composite nanosheet. The TEM image is as follows Fig.10 As shown, it indicates that the carbon material obtained after high-temperature calcination maintains the original structure, uniformity and dispersibility, and the mesopore size is slightly reduced.

[0035] Comparative Example 1 Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water. Stir at 40 °C for 2 h, then add 120 mg of MXene powder and stir at 40 °C for 1 h. Add 100 mg of dopamine and continue stirring for 1 h. Adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 12 h. After centrifugation and drying, two-dimensional mesoporous composite nanosheets are obtained.

[0036] The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this comparative example are as follows: Fig.11 As shown, it can be seen that the prepared material has poor dispersibility and the mesopores are not obvious compared with the examples.

[0037] Comparative Example 2 Weigh 1 g of α-sulfo fatty acid methyl ester (mono) sodium salt and dissolve it in 1000 mL of deionized water, stir at 40 °C for 2 h, then add 120 mg of MXene powder, stir at 40 °C for 1 h, add 100 mg of polyvinyl alcohol, and continue stirring for 1 h; adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h. After centrifugation and drying, a two-dimensional mesoporous composite nanosheet was obtained; The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this comparative example are as follows: Fig.12 As shown, it can be seen that the prepared material has poor dispersibility and a disordered mesoporous structure.

[0038] Comparative Example 3 Weigh 1 g of Pluronic P-123 and dissolve it in 1000 mL of deionized water. Stir at 40 °C for 2 h, then add 120 mg of MXene powder and stir at 40 °C for 1 h. Add 100 mg of polyvinyl alcohol and continue stirring for 1 h. Adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h. After centrifugation and drying, a two-dimensional mesoporous composite nanosheet was obtained. The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this comparative example are as follows: Fig.13 As shown, it can be seen that the prepared material has poor dispersibility and a disordered mesoporous structure with a mesopore diameter of about 10 nanometers.

[0039] Comparative Example 4 Weigh 1 g of Pluronic F-127 and dissolve it in 1000 mL of deionized water. Stir at 40 °C for 2 h, then add 120 mg of MXene powder and stir at 40 °C for 1 h. Add 100 mg of polyvinyl alcohol and continue stirring for 1 h. Adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h. After centrifugation and drying, a two-dimensional mesoporous composite nanosheet was obtained. The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this comparative example are as follows: Fig.14 As shown, it can be seen that the prepared material has good dispersion and uniformity and has a mesoporous structure.

[0040] Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water. Stir at 25 °C for 2 h, then add 120 mg of MXene powder and stir at 25 °C for 1 h. Add 100 mg of polyvinyl alcohol and continue stirring for 1 h. Adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h. After centrifugation and drying, a two-dimensional mesoporous composite nanosheet is obtained. The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this comparative example are as follows: Fig.15 As shown, it can be seen that the prepared material has poor dispersibility and a disordered mesoporous structure.

[0041] Comparative Example 6 Weigh 1 g of hexadecylaminomethane and dissolve it in 1000 mL of deionized water. Stir at 60 °C for 2 h, then add 120 mg of MXene powder, stir at 60 °C for 1 h, add 100 mg of polyvinyl alcohol, and continue stirring for 1 h. Adjust the pH value of the solution to 8.5, initiate the polymerization reaction, and stir for 8 h. After centrifugation and drying, a two-dimensional mesoporous composite nanosheet was obtained; The TEM images of the two-dimensional mesoporous composite nanosheets prepared in this comparative example are as follows: Fig.16 As shown, it can be seen that the prepared material has a mesoporous structure, but the micelle distribution is uneven.

[0042] After carbonizing the two-dimensional mesoporous composite nanosheet material obtained in Example 1 at 400° C., 80 mg of the sample was weighed and mixed with paraffin wax in a ratio of 1:1, and then placed in a mold and pressed into a ring. A vector network analyzer was used for testing.

[0043] Test results see Fig.17 As shown, the strongest reflection loss of the embodiment of the present invention is as high as -54.2 dB, and has a sufficiently wide EAB (3.1 GHz), so that effective absorption can be achieved in a wider frequency band. Therefore, the two-dimensional mesoporous composite nanosheet material prepared by the present invention has a good effect as an absorbing material.

[0044] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing polymer-MXene-polymer heterostructure nanosheets, characterized in that: The following steps are involved: After the template and the reaction solvent are mixed, two-dimensional MXene nanosheets and resin are added in sequence to obtain a reaction solution, and the reaction solution is subjected to a polymerization reaction; After the reaction is completed, the obtained reaction product is subjected to post-treatment and calcination treatment in sequence to obtain polymer-MXene-polymer heterostructure nanosheets.

2. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The template agent is a surfactant; The surfactant is one of hexadecylaminomethane, sodium α-olefin sulfonate, sodium linear alkylbenzene sulfonate, sodium α-sulfonated fatty acid methyl ester (mono) sodium salt, fatty acid polyoxyethylene ester, Pluronic P-123 and Pluronic F-127; The resin is one or more of polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, dopamine and phenolic resin.

3. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The reaction solvent is water.

4. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The mass concentration of the resin in the reaction solution is 0.5-10 g / L.

5. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The mass concentration of the template in the reaction solution is 1-10 g / L.

6. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: During the polymerization reaction, the mass concentration ratio of the resin to the template agent is 0.1-100.

7. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The polymerization reaction temperature is 25-80°C and the reaction time is 2-72 hours.

8. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The calcination treatment is carried out in an inert atmosphere; the temperature of the calcination treatment is 300-1800°C, and the time is 1-24 hours; the inert atmosphere is nitrogen or argon.

9. The method for preparing a polymer-MXene-polymer heterostructure nanosheet according to claim 1, characterized in that: The post-treatment includes centrifugation and drying processes performed sequentially.

10. A polymer-MXene-polymer heterostructure nanosheet, characterized in that: The method is prepared by any one of claims 1 to 9.